IMPLEMENTASI PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN MODEL PEMBELAJARAN KONVENSIONAL TERHADAP KEMAMPUAN SISWA DALAM MENENTUKAN STRUKTUR TEKS CERITA PENDEK SISWA KELAS XI SMA NEGERI 1 BESITANG TAHUN PEMBELAJARAN 2024-2025 - Sulismawati; Rahmat Kartolo; Sutikno; Ahmad Laut Hasibuan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine whether the influence of the Problem Based Learning approach is higher than the Conventional approach on the ability to determine the structure of short story texts of class XI students of SMA Negeri 1 Besitang in the 2024-2025 academic year. The population in this study was the population in this study were all class XI students of SMA Negeri 1 Besitang in the 2024-2025 academic year, with a sample of 40 people, namely class XI. The method used in this study was an experimental method with a two-group pre-test post-test design approach to determine the effect of the Problem Based Learning approach being higher than the Conventional approach on the ability to determine the structure of short story texts of class XI students of SMA Negeri 1 Besitang in the 2024-2025 academic year. The results showed that the ability to determine the structure of short story texts using conventional in class XI students of SMA Negeri 1 Besitang in the 2024-2025 academic year was classified as sufficient with an average value of 66.85. The ability to determine the structure of short story texts using the Problem Based Learning approach in class XI students of SMA Negeri 1 Besitang in the 2024-2025 academic year is categorized as good with an average value of 72.07. It can be concluded that there is a higher influence of the Problem Based Learning approach than the Conventional approach on the ability to determine the structure of short story texts in class XI students of SMA Negeri 1 Besitang in the 2024-2025 academic year. The use of the Problem Based Learning approach to improving the ability to determine the structure of short story texts is more effective than the conventional method.